2021
DOI: 10.1038/s41598-021-93067-1
|View full text |Cite
|
Sign up to set email alerts
|

Extended JAZ degron sequence for plant hormone binding in jasmonate co-receptor of tomato SlCOI1-SlJAZ

Abstract: Abstract(+)-7-iso-Jasmonoyl-l-isoleucine (JA-Ile) is a lipid-derived phytohormone implicated in plant development, reproduction, and defense in response to pathogens and herbivorous insects. All these effects are instigated by the perception of JA-Ile by the COI1-JAZ co-receptor in the plant body, which in Arabidopsis thaliana is profoundly influenced by the short JAZ degron sequence (V/L)P(Q/I)AR(R/K) of the JAZ protein. Here, we report that SlJAZ-SlCOI1, the COI1-JAZ co-receptor found in the tomato plant, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…These proteins are critical for protein-protein interactions with COI1, which creates the COI1-JA-Ile-JAZ co-receptor complex with the JA-Ile (jasmonoyl-L-isoleucine) ligand and then forms the COI1-JAZ co-receptor complex with the COI1-JA-Ile-JAZ co-receptor complex ( Chini et al., 2007 ; Thines et al., 2007 ; Yan et al., 2007 ; Bai et al., 2011 ). The sensing of JA-Ile by the COI1-JAZ co-receptor in the plant body causes stress reactions ( Saito et al., 2021 ). JAZ1-7, 9-12 mutations in Arabidopsis improve JA responses while suppressing COI1 phenotypes in flowering time, rosette expansion, and defense ( Liu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are critical for protein-protein interactions with COI1, which creates the COI1-JA-Ile-JAZ co-receptor complex with the JA-Ile (jasmonoyl-L-isoleucine) ligand and then forms the COI1-JAZ co-receptor complex with the COI1-JA-Ile-JAZ co-receptor complex ( Chini et al., 2007 ; Thines et al., 2007 ; Yan et al., 2007 ; Bai et al., 2011 ). The sensing of JA-Ile by the COI1-JAZ co-receptor in the plant body causes stress reactions ( Saito et al., 2021 ). JAZ1-7, 9-12 mutations in Arabidopsis improve JA responses while suppressing COI1 phenotypes in flowering time, rosette expansion, and defense ( Liu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jasmonates are lipid‐derived hormones that play essential roles in plant development and defence against herbivores and necrotrophic pathogens (Howe et al ., 2018; Wasternack & Feussner, 2018). Extensive studies on angiosperms, mainly Arabidopsis thaliana , identified (+)‐7‐ iso ‐JA‐Ile as the ligand of the jasmonate co‐receptor complex formed by the F‐box coronatine insensitive 1 (COI1) and the jasmonate ZIM domain (JAZ) repressors (Xie et al ., 1998; Chini et al ., 2007; Thines et al ., 2007; Katsir et al ., 2008; Fonseca et al ., 2009; Sheard et al ., 2010; Fu et al ., 2021; Saito et al ., 2021). More recently, studies in the bryophyte Marchantia polymorpha and the lycophyte Huperzia selago identified two isomers of dn‐OPDA: dn‐ cis ‐OPDA and dn‐ iso ‐OPDA as the COI1/JAZ ligands in both species, and Δ 4 ‐dn‐ iso ‐OPDA as an additional ligand in M. polymorpha (Monte et al ., 2018, 2022; Kneeshaw et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…3) 32 . Based on this result, we reported the affinity between 1/2 and SlCOI1-SlJAZ pairs using GST-SlCOI1 and fluorescein-labeled SlJAZ degron short peptides (Fl-SlJAZPs) 39 . According to this previous report, SlJAZ12 was excluded in the FA assay because it does not have a conserved JAZ degron sequence 32 .…”
Section: Resultsmentioning
confidence: 97%